“Creating spaces to strengthen life skills preventing drug use in adolescence and youth” (a project run by the University of Costa Rica, 2018-2019): An analysis of the TC687 from the methodology of the systematization of experiences - Martínez Esquivel, Daniel (2020)
This research reconstructs the experience of the social work project #TC687 to strengthen life skills, run by the University of Costa Rica from 2018 to 2019. To strengthen the social participation of university students that contribute to meeting the needs of Costa Rican communities. Systematization of experiences based on the proposal by Óscar Jara (2012) as a methodological strategy. To collect the information, learning recovery sheets were used. Students’ participation was based on prior training to perform fieldwork, besides the diagnosis, planning, execution, evaluation, and registration of educational strategies with a focus on life skills that prevent drug use in populations at risk. The TC687 project strengthens student participation by bringing it closer to different realities that sensitize it to people and their needs. In addition, from experience, both students and the community strengthen life skills.